Thermal performance of a fully developed serpentine wavy channel solar air heater. (October 2019) - Singh, Satyender; Singh, Ankit; Chander, Subhash
Highlights: A fully developed serpentine wavy channel solar air heater is considered. Experimental and numerical investigations are carried out. Experimental results revealed the air heating potential of the solar air heater. Numerical results present the physics involved. Occurrence of secondary flow in the channel promotes heat transfer. Abstract: Thermal performance of a fully-developed serpentine wavy channel solar air heater is investigated experimentally and numerically for the mass flow rate ranging from 0.01 kg/s to 0.04 kg/s. Solar air heater consists of three air heating channels. However, only serpentine wavy channel is operated for the forced convection to provide the hot air at high flow rates. The natural convection incurred inside both the first and third closed channels. The first channel is utilized to reduce the top losses, while the thermal gain by air due to natural convection in the third channel is examined to utilize for thermal applications. Experimental results revealed the potential of the serpentine wavy channel in the thermal performance enhancement. Whereas, the maximum outlet air temperature of 54 °C is obtained corresponding to solar radiations of about 831 W/m 2 and mass flow rate of 0.01 kg/s, while it is 52 °C in the third channel. Although, the maximum thermal efficiency and the pressure drop of 66% and 3 Pa, respectively, is obtained at a mass flow rate of 0.04 kg/s. Moreover, numerical results depict that the occurrence of flow circulation in the second and third channels is responsible for the high thermal performance of the present solar air heater. Optimization of geometrical parameters is also presented in the extent of the numerical investigation.